A phase 2 study of oral difelikefalin in subjects with chronic kidney disease and moderate-to-severe pruritus - Yosipovitch, Gil; Awad, Ahmed; Spencer, Robert H.; Munera, Catherine; Menzaghi, Frédérique (Journal of the American Academy of Dermatology, 2023)
Chronic pruritus is burdensome for patients with chronic kidney disease (CKD). We evaluated difelikefalin efficacy and safety in reducing itch in subjects with non–dialysis-dependent CKD and those undergoing hemodialysis (HD). This phase 2, double-blind, randomized, placebo-controlled, dose-finding study enrolled non–dialysis-dependent CKD (stage 3-5) and HD subjects with moderate-to-severe pruritus. Subjects were equally randomized to oral difelikefalin (0.25, 0.5, or 1.0 mg) or placebo once daily for 12 weeks. The primary end point was the change in the weekly mean Worst Itching Intensity Numeric Rating Scale (WI-NRS) score at week 12. Two hundred sixty-nine subjects were randomized (mean [SD] baseline WI-NRS: 7.1 [1.2]). Difelikefalin 1.0 mg significantly reduced weekly mean WI-NRS scores versus placebo at week 12 (P = .018), with numerical reductions observed with difelikefalin 0.25 and 0.5 mg. At week 12, 38.6% of subjects receiving difelikefalin 1.0 mg achieved a complete response (WI-NRS 0-1) versus 14.4% receiving placebo. Difelikefalin resulted in ∼20% improvement in itch-related quality-of-life measures. The most common treatment-emergent adverse events were dizziness, fall, constipation, diarrhea, gastroesophageal reflux disease, fatigue, hyperkalemia, hypertension, and urinary tract infection. Study duration was 12 weeks. Oral difelikefalin significantly reduced itch intensity in stage 3-5 CKD subjects with moderate-to-severe pruritus, supporting continued development for this condition.